Employment policy in the COVID-19 - Nosova, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The paper analyses the macroeconomic situation in the labor market and proposes measures to restore employment to the pre-COVID -19 level. The study of the basic concepts of state regulation methods of employment demonstrates that various forms of their application are used on the country’s macroeconomic level. In developing countries long-term COVID-19 related restrictive measures result in the dramatic decline of economic activity, contraction of production, unemployment rise, drop in labor productivity. The countries with high macroeconomic indicators have better social cohesion and reliable systems of social protection. This has consequences that are more reliable on the employment level compared to the developing countries. Assessment of various policy approaches of full lockdown measures for localization of disease dissemination, imposition of restrictions on the working life, introduction of new remote forms of work and education, force countries to define special policy, which depends on the national economic and financial potential. Health system development and adoption of stabilizing measures of the epidemic situation in the country form the basis to restore confidence and trust in the society. The article proposes a deep account of the challenges that the Ukrainian economy has faced and continues to face due to the COVID-19 pandemic effects, deterioration of macroeconomic indicators, including employment decline. The application of the “adaptive quarantine measures” in the regions demonstrates adequate consequences for business SME's development. The estimation results depict the tendencies of increasing unemployment, inflation, and a decreasing population’s ability to pay and lowering business activity in certain sectors of the economy. Numerous forms related to the support and professional development of the unemployed population are proposed.